The role of equity in the relationship between job evaluation and employee performance in Jordan Industrial Estates - Khtatbeh, Mohamed Mahmoud; Mahomed, Anuar Shah Bali; Ab Rahman, Suhaimi; Mohamed, Rosmah (Inderscience, 2022)
This study aimed to assess the extent of the mediation effect of equity on the relationship between job evaluation and employee performance. A self-administrated questionnaire was used to collect data from 646 employees working in the targeted industrial estates. The collected data was analysed using SPSS and AMOS software tools based on structural equation modelling (SEM). The results of the study indicated to a non-significant relationship between job evaluation and job performance. On the other hand, a significant relationship was found between equity and job performance as well as between job evaluation and equity. Moreover, the results of the study demonstrated a mediation role of equity on the relationship between job evaluation and job performance. The results of this study are expected to have a significant influence in filling the gap in the literature and enhancing employees' performance accordingly.